Covid-19 Archives And Social Capital As Learning Source In Post-Pandemic History Education In Indonesia - Nour Muhammad Adriani; Labibatussolihah Labibatussolihah (Universitas Pahlawan Tuanku Tambusai, 2023)
The Covid-19 pandemic is a period of challenges that are pressing the social capital of the nations around the world, including Indonesia. Archives, as a portrait of society and its history, of course, have a role in the revitalization of this network or social capital. How can education utilize Covid-19 archives in increasing social capital to deal with the pandemic and post-pandemic recovery? This paper presents a context-based-learning strategy in modern pedagogy to achieve two goals: the utilization of social capital and the development of national cohesiveness, which is used as an alternative in an emergency. It is obvious that the Covid-19 archives are highly potential to develop solidarity across national and beyond national borders. Here, we discuss how national and global responsiveness will add value to social capital at the regional, cultural, communal, and personal levels. It is hoped that with this strategy, post-pandemic social recovery will be accelerated where national interests move simultaneously with a more coherent discourse of identity and global solidarity.